METODOLOGI PENELITIAN HADIS:ANTARA KRITIK SANAD DAN MATAN - Rahman; Imelda Putri Hsb; Maya Fitri Sulastri (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
This study aims to examine the methodology of hadith research, focusing on two important aspects in hadith criticism, namely sanad criticism and matan criticism. The methodology used is a literature approach, which relies on the study of classical and contemporary sources related to criticism of both. Analysis of sanad criticism focuses on verifying the path of hadith transmission, while matan criticism emphasizes more on the validity of the content and its conformity with the principles of Islamic teachings. The results of this study indicate that both aspects have a very important role in ensuring the quality and validity of hadith as a source of law and teachings in Islam. This study also provides insight into how the sanad and matan criticism methods can be applied in hadith studies in the modern era.